A framework for development and test of XTCA modules with FPGA based systems for particle detectors∗ - Paiva, T. C.; Ramalho, L. A.; Shinoda, A. A.; Cascadan, A. [UNESP]; Ferreira, V. F. [UNESP]; Vaz, M. [UNESP] (My University, 2016)
This work describes a framework to develop firmware for ATCA carrier boards with FPGA. It is composed of an ATCA IPMI protocol implementation for environmental monitoring and control, and a companion XVC protocol implementation for remote FPGA configuration and system debugging. A study case is also presented of the development of a setup to validate a Level 1 Tracker Trigger System proposed for CMS at HL-LHC.